A novel sulfur mustard (HD) vapor inhalation exposure model of pulmonary toxicity for the efficacy evaluation of candidate medical countermeasures. (3rd July 2021) - Perry, Mark R.; Neal, Matthew; Hawks, Roger; Pressburger, David; Satola, Jan; Triplett, Cheryl; Reed, Beth; Andrews, Meredith; Harvilchuck, Jill A.; Nealy, Michael S.; Platoff, Gennady E.; Yeung, David T.
Abstract: Objective: To develop a novel inhalation exposure system capable of delivering a controlled inhaled HD dose through an endotracheal tube to anesthetized rats to investigate the lung pathophysiology and evaluate potential medical countermeasures. Materials and methods: Target HD vapor exposures were generated by a temperature-controlled vapor generator, while concentration was monitored near real-time by gas chromatography. Animal breathing parameters were monitored real-time by in-line EMKA/SciReq pulmonary analysis system. Individual exposures were halted when the target inhaled doses were achieved. Animals were observed daily for clinical observations and lethality with scheduled termination at 28 days post-exposure. Upon scheduled or unscheduled death, animals underwent a gross necropsy and lung and trachea were collected for histopathology. Results: Controlled HD concentrations ranged from 60 to 320 mg/m 3 . Delivered inhaled doses range from 0.3 to 3.20 mg/kg with administered doses within 3% of the target. The 28-day inhaled LD50 is 0.80 mg/kg (95% CI = 0.42–1.18 mg/kg). Post exposure respiratory abnormalities were observed across all dose levels though the higher dose levels had earlier onset and higher frequency of occurrence. Histopathologic alterations were not qualitatively altered in accordance with dose but instead showed a relationship to an animals' time of death, with early deaths demonstrating acute damage and later deaths displaying signs of repair. Discussion/Conclusion: This novel exposure system administers targeted HD inhaled doses to generate a small animal model that can be used to evaluate physiological toxicities of inhaled HD on the lungs and for evaluation of potential medical countermeasure treatments.